Neutrophil-to-lymphocyte ratio in predicting prognosis and course of community community-acquired pneumonia in hospitalized patients. - T. O. Pertseva; T. V. Kirieieva; K. O. Bielosludtseva; M. A. Krykhtina (Medičnì Perspektivi)
Currently, a marker which could be used both to assess the severity of community acquired pneumonia (CAP) and determine the risk of complications is being searched. According to some authors, Neutrophil-to-Lymphocyte Ratio (NLR) could be such a marker. Therefore, the aim of our research was to determine the diagnostic significance of NLR in patients with CAP and to establish the relationship of NLR with other clinical and laboratory parameters. We conducted a retrospective analysis of 171 case histories of patients with CAP of 3 and 4 clinical groups, with the calculation of NLR (according to the common blood count). In the course of the work, it was found that NLR reflects a balance between the response of neutrophils and lymphocytes and this parameter is associated with the severity of systemic inflammation in patients with CAP. NLR has good diagnostic value in determining the mortality risk in patients with CAP, specially an increase in the level of NLR (more than 10) is associated with a high risk of life-threatening complications.